Portable hyperbaric chambers for the treatment of altitude disease - Thomas Küpper; Ulf Gieseler; Jim Milledge; Audry Morrison; Volker Schöffl (University of Applied Sciences in Tarnow, Poland, 2022)
Portable hyperbaric chambers are a therapeutic option for altitude disease in the mountains. By an increase of the oxygen partial pressure the patient's symptoms ameliorate significantly. Portable hyperbaric chambers may be used as 'stand alone therapy' as well as in combination with other therapeutic options. Here we present the recommendation how to use the device and how to avoid problems. The recommendation has been agreed by all members of the medical commission of the world umbrella organization Union Internationale des Associations d'Alpinisme (UIAA MedCom).